Effect of replacing barley grain with cork oak acorn (Quercus Suber L.) on digestibility, nitrogen balance and growth of goat kids. - Aziza, G. B.; Hedi, A.; Hajer, K.; Rabia, M. (JOURNAL OF ANIMAL SCIENCE, 2006)
The objective of this study was to evaluate the effect of the replacement of barley grain with cork oak acorn (Quercus suber L.) on performance, nutrients intakes, apparent digestibility coefficient and nitrogen balance with growing goats. Ten Boer kids (26.5±2 kg) were individually housed in metabolism cages and were randomly divided into a control (n = 5) and an experimental (n = 5) group. Kids in both groups received (on the basis of crude matter) 500 g/day per head of chopped oat hay and 600 g of concentrate containing barley grain (control group) or oak acorn (experimental group). Digestibility coefficients of dietary components were reduced as a result of acorn substitution for barley. Nitrogen retention (g/day) was positive for experimental group (6.18) but lower than for control group (8.72). The average consumption of digestible components, expressed in g kg-1 LW 0.75 for the control and experimental groups was, respectively, 51.5 and 41.5 (OM) and 7.9 and 6.0 (CP), resulting in weight gains of 80 and 43 g/day.
The following values have no corresponding Zotero field: pub-location: 1111 NORTH DUNLAP AVE, SAVOY, IL 61874 USA publisher: AMER SOC ANIMAL SCIENCE
Keywords: digestibility; kids; oak acorn

Effect of replacing barley grain with cork oak acorn (Quercus Suber L.) on digestibility, nitrogen balance and growth of goat kids. - Aziza, G B; Hedi, A; Hajer, K; Rabia, M (JOURNAL OF ANIMAL SCIENCE, 2006)
The objective of this study was to evaluate the effect of the replacement of barley grain with cork oak acorn (Quercus suber L.) on performance, nutrients intakes, apparent digestibility coefficient and nitrogen balance with growing goats. Ten Boer kids (26.5±2 kg) were individually housed in metabolism cages and were randomly divided into a control (n = 5) and an experimental (n = 5) group. Kids in both groups received (on the basis of crude matter) 500 g/day per head of chopped oat hay and 600 g of concentrate containing barley grain (control group) or oak acorn (experimental group). Digestibility coefficients of dietary components were reduced as a result of acorn substitution for barley. Nitrogen retention (g/day) was positive for experimental group (6.18) but lower than for control group (8.72). The average consumption of digestible components, expressed in g kg-1 LW 0.75 for the control and experimental groups was, respectively, 51.5 and 41.5 (OM) and 7.9 and 6.0 (CP), resulting in weight gains of 80 and 43 g/day.
Keywords: digestibility; kids; oak acorn